2014
DOI: 10.1177/2047487314540546
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of functional electrical stimulation of lower limb muscles in elderly patients with chronic heart failure: A pilot study

Abstract: In this pilot study, FES effectively improved functional status, quality of life, motional stress and endothelial function in elderly chronic heart failure patients and warrants further investigation in this particular group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
18
1
5
Order By: Relevance
“…Patients who did not receive any kind of intervention were included in the control group (n=271). Patients who received 30 min a day (individually), 5-days/week FES for 12 weeks (9) were included in the FES group (n=271). Patients who received 1-h group classes of TC exercise twice weekly for 12 weeks (12) were included in the TCE group (n=271).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who did not receive any kind of intervention were included in the control group (n=271). Patients who received 30 min a day (individually), 5-days/week FES for 12 weeks (9) were included in the FES group (n=271). Patients who received 1-h group classes of TC exercise twice weekly for 12 weeks (12) were included in the TCE group (n=271).…”
Section: Methodsmentioning
confidence: 99%
“…Eight 60-mm adhesive electrodes were placed on the skin over the lower medial and upper lateral parts of the quadriceps muscle and over the lower and upper portions of the gastrocnemius muscles. A direct electrical current at 25 Hz was applied for 5 s. A 5-s interval was allowed between the two currents (9). RehaMove ® FES Cycling instrument (HASOMED GmbH, Germany) was used for all patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifactorial pathophysiology of HFpEF needs to be investigated in depth. Particularly, therapies targeting skeletal muscle dysfunction warrant further evaluation . Furthermore, industrial research should set a high priority in developing and evaluating new pharmaceutical agents for these patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…In this particular CHF population, who are unable to perform conventional exercise, FES may serve as an alternative mode of training. As previously emphasized, FES is an easily applicable, well‐tolerated and safe modality in a wide range of HF patients, including elderly ones and those with severe symptoms [New York Heart Association (NYHA) class III or IV] . In addition, it has been shown that FES might exert a greater benefit on clinical and neurohormonal parameters in NYHA III–IV patients compared with NYHA II patients .…”
mentioning
confidence: 99%